2020
DOI: 10.1155/2020/4934206
|View full text |Cite
|
Sign up to set email alerts
|

Association of WISP1/CCN4 with Risk of Overweight and Gestational Diabetes Mellitus in Chinese Pregnant Women

Abstract: Background. Obese women with gestational diabetes mellitus (GDM) have a higher risk of adverse outcomes than women with obesity or GDM alone. Our study is aimed at investigating the discriminatory power of circulatory Wnt1-inducible signaling pathway protein-1 (WISP1), a novel adipocytokine, on the copresence of prepregnancy overweight/obesity and GDM and at clarifying the relationship between the WISP1 level and clinical cardiometabolic parameters. Methods. A total of 313 participants were screened from a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The role of F2 in hypercoagulation is already known [12]. Other studies have confirmed the importance of F2 in patients with diabetes [14,15]. As was previously reported, prothrombin fragment F2 is a polypeptide fragment produced by the factor Xa complex after hydrolyzing prothrombin during blood coagulation [13].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The role of F2 in hypercoagulation is already known [12]. Other studies have confirmed the importance of F2 in patients with diabetes [14,15]. As was previously reported, prothrombin fragment F2 is a polypeptide fragment produced by the factor Xa complex after hydrolyzing prothrombin during blood coagulation [13].…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies also indicated metabolic abnormalities in GDM patients. For example, in GDM patients, higher concentrations of HDL were observed in the third trimester of pregnancy, and higher triglyceride levels were found in both the second and third trimesters [14]. Therefore, the hypercoagulable status of GDM patients might be alleviated by targeting miR-451a.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt1-inducible signaling pathway protein-1 (WISP1) was studied by Liu et al [ 330 ] in 313 pregnant women (GDM n = 61, 2 h 75 g OGTT, IADPSG criteria). The samples were taken at the time of the OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of GDM is quickly rising in the context of the global obesity epidemic [ 48 , 49 ]. GDM is described as carbohydrate intolerance of variable severity with onset or first detection during pregnancy [ 50 ], encompassing abnormal glucose tolerance and diabetes mellitus, which was undiagnosed prior to or began concomitantly during pregnancy [ 51 ]. Besides, epigenetic modification plays a critical role in multiple fundamental cellular processes [ 52 ], in which epigenetic alterations are involved in the early stage of metabolic diseases including GDM [ 53 ].…”
Section: Discussionmentioning
confidence: 99%